Pasierb – eseista. Stan posiadania, perspektywy badawcze - Kudyba, Wojciech (Colloquia Litteraria, 2014)
Pasierb – an essayist. What we have and the research prospects Even though Fr. Janusz Stanisław Pasierb’s essay books enjoyed considerable popularity already during the author’s lifetime and they account for a sizeable portion of his writings, they have not been a subject of a separate study yet. Recently published Ars, fides et ratio. Esej teologiczny? (Tischner – Pasierb – Szymik) (Siedlce, 2012) [Ars, fides et ratio. A theological essay? (Tischner – Pasierb – Szymik)] by Aleksandra Pethe awakens hope for a revival in interest in Fr. Pasierb’s essays. The book itself contributes very little to the research on the writer’s essays, however it does pose important questions, among others on the mechanisms of the essayisation of homilies employed by Fr. Pasierb. It seems that other ways in which he transgressed various literary forms in the direction of theological essay deserve special attention. Fr. Pasierb’s writings remain open to state-of-the-art research tools and call for urgent investigation.